Estimasi Produksi Jagung (Zea Mays L.) Menggunakan Pendekatan Ekologi Spasial Di Kabupaten Jeneponto - Laode Muhamad Irsan; Rahma Musyawarah; Amniar Ati (Jambura Geoscience Review, 2020)
Jeneponto Regency is one of the biggest corn producers in South Sulawesi. Jeneponto Regency is the most suitable area for estimating corn crop production because it is the largest corn-producing region in South Sulawesi Province and has quite complex terrain variations. Agricultural management requires accurate and accurate information or data that can increase productivity and economic benefits. Get accurate and up-to-date data or information about parts of an accurate agricultural information system to support proper planning. The purpose of this study is to map climatic conditions (rainfall) and physical conditions (slope, height, soil type) and to estimate the amount of corn production and maize production maps through spatial assessment. This research was conducted in the Jeneponto Regency, which is located in the southern part of the South Sulawesi Province. The results of the study show that spatial ecology based on agro-ecosystem zones or agricultural unit units in the estimation of special maize production can increase estimation results with high accuracy. Based on the analysis of the four physical maps that have been mapped are rainfall, soil type, slope, and height which are regulated in the agro-ecosystem zone, the estimated amount with spatial ecological calculations is 159.584,05 tons. The accuracy of the estimation model results with field data reaches 95%. Based on the results of the study can conclude the results of spatial ecological research can be used as a method of estimating production on corn.